UNIT IE.9 Production of 3‐D Airway Organoids From Primary Human Airway Basal Cells and Their Use in High‐Throughput Screening. (12th May 2016) - Hild, Marc; Jaffe, Aron B.
Abstract : The ability of human airway basal cells to serve as progenitor cells in the conducting airway makes them an attractive target in a number of respiratory diseases associated with epithelial remodeling. This unit describes a protocol for the culture of 'bronchospheres', three‐dimensional (3‐D) organoids that are derived from primary human airway basal cells. Mature bronchospheres are composed of functional multi‐ciliated cells, mucin‐producing goblet cells, and airway basal cells. In contrast to existing methods used for the culture of well‐differentiated human airway epithelial cells, bronchospheres do not require growth on a permeable support and can be cultured in 384‐well assay plates. The system provides a mechanism for investigating the regulation of basal cell fate during airway epithelial morphogenesis, as well as a basis for studying the function of the human airway epithelium in high‐throughput assays. © 2016 by John Wiley & Sons, Inc.